Modulation of electrocaloric effect and nanodomain structure in Mn-doped Pb(In0.5Nb0.5)O3-PbTiO3 ceramics. Issue 16 (November 2018) - Qiao, Huimin; He, Chao; Zhuo, Fangping; Wang, Zujian; Li, Xiuzhi; Liu, Ying; Long, Xifa
Abstract: The combination of electrocaloric (EC) and negative electrocaloric (NEC) effect in ferroelectrics is highly desirable for improving refrigerating efficiency and cooling capacity. However, the NEC effect is very rare because polarization decreases at elevated temperatures. In this work, the NEC effect in acceptor-doped ferroelectric ceramics with ABO3 perovskite structure was designed and simulated through a phenomenological model based on the Ginzburg-Landau-Devonshire theory. The coexistence of EC-NEC effects and enhanced wide range NEC effect were achieved in Mn-doped Pb(In0.5 Nb0.5 )O3 -PbTiO3 (PINT) ceramic by adjusting defect dipoles. The virgin PINT ceramic only has positive EC effect (Δ T = 0.63 °C, under 40 kV/cm at 260 °C). However, coexistence of multiple EC and NEC was obtained in PINTMn4, which is valuable in improving the electrocaloric efficiency and cooling capacity. In PINTMn6, a single NEC effect was observed over a wide operating temperature range, from room temperature to 200 °C, and Δ T = − 0.62 °C was achieved at 173 °C, under an electric field of 40 kV/cm. In addition, similar island domain patterns were observed using piezoresponse force microscopy. The coexistence of positive and negative effects enhanced the NEC effect and a wide operating temperature range obtained in Mn-doped PINT bulk ceramic may aid in the development of high-efficiency solid-state cooling devices.